Crowd Management Strategies Employed During A Football Match: A Case study (Media Ilmu Keolahragaan Indonesia, 2022)
Workers at stadiums and arenas are critical components of any approach to preventing crowd violence. This study describes the crowd management strategies employed at football matches held at Jakarta's Gelora Bung Karno International Stadium. This qualitative study examines crowd management tactics used before football games to explain crowd management strategies used throughout the game and strategies used to disperse and evacuate crowds during football events. A random sample of fifteen managers, eighteen technical personnel, fourteen support workers, and two hundred and twenty-seven police officers is taken. Questionnaires and interview protocols were used to collect data. The researcher develops structured or open-ended questions based on various subject areas, including demographic data, stadium safety features, pre-event techniques, crowd management strategies during sporting events, and post-event management strategies. The findings reveal that seven crowd management measures were utilized prior to the event, three were used during the event, and three were used to disperse and evacuate individuals at Gelora Bung Karno. There are implications and recommendations made.